DEFINITION clear_gen_flat()
TYPE =
∀f:F.∀e:C.∀x:C.∀u:T.(clear (CHead e (Flat f) u) x)→(clear e x)
BODY =
assume f: F
assume e: C
assume x: C
assume u: T
suppose H: clear (CHead e (Flat f) u) x
assume y: C
suppose H0: clear y x
we proceed by induction on H0 to prove (eq C y (CHead e (Flat f) u))→(clear e x)
case clear_bind : b:B e0:C u0:T ⇒
the thesis becomes
∀H1:eq C (CHead e0 (Bind b) u0) (CHead e (Flat f) u)
.clear e (CHead e0 (Bind b) u0)
suppose H1: eq C (CHead e0 (Bind b) u0) (CHead e (Flat f) u)
(H2)
we proceed by induction on H1 to prove
<λ:C.Prop>
CASE CHead e (Flat f) u OF
CSort ⇒False
| CHead k ⇒<λ:K.Prop> CASE k OF Bind ⇒True | Flat ⇒False
case refl_equal : ⇒
the thesis becomes
<λ:C.Prop>
CASE CHead e0 (Bind b) u0 OF
CSort ⇒False
| CHead k ⇒<λ:K.Prop> CASE k OF Bind ⇒True | Flat ⇒False
consider I
we proved True
<λ:C.Prop>
CASE CHead e0 (Bind b) u0 OF
CSort ⇒False
| CHead k ⇒<λ:K.Prop> CASE k OF Bind ⇒True | Flat ⇒False
<λ:C.Prop>
CASE CHead e (Flat f) u OF
CSort ⇒False
| CHead k ⇒<λ:K.Prop> CASE k OF Bind ⇒True | Flat ⇒False
end of H2
consider H2
we proved
<λ:C.Prop>
CASE CHead e (Flat f) u OF
CSort ⇒False
| CHead k ⇒<λ:K.Prop> CASE k OF Bind ⇒True | Flat ⇒False
that is equivalent to False
we proceed by induction on the previous result to prove clear e (CHead e0 (Bind b) u0)
we proved clear e (CHead e0 (Bind b) u0)
∀H1:eq C (CHead e0 (Bind b) u0) (CHead e (Flat f) u)
.clear e (CHead e0 (Bind b) u0)
case clear_flat : e0:C c:C H1:clear e0 c f0:F u0:T ⇒
the thesis becomes ∀H3:(eq C (CHead e0 (Flat f0) u0) (CHead e (Flat f) u)).(clear e c)
(H2) by induction hypothesis we know (eq C e0 (CHead e (Flat f) u))→(clear e c)
suppose H3: eq C (CHead e0 (Flat f0) u0) (CHead e (Flat f) u)
(H4)
by (f_equal . . . . . H3)
we proved
eq
C
<λ:C.C> CASE CHead e0 (Flat f0) u0 OF CSort ⇒e0 | CHead c0 ⇒c0
<λ:C.C> CASE CHead e (Flat f) u OF CSort ⇒e0 | CHead c0 ⇒c0
eq
C
λe1:C.<λ:C.C> CASE e1 OF CSort ⇒e0 | CHead c0 ⇒c0 (CHead e0 (Flat f0) u0)
λe1:C.<λ:C.C> CASE e1 OF CSort ⇒e0 | CHead c0 ⇒c0 (CHead e (Flat f) u)
end of H4
(h1)
(H5)
by (f_equal . . . . . H3)
we proved
eq
F
<λ:C.F>
CASE CHead e0 (Flat f0) u0 OF
CSort ⇒f0
| CHead k ⇒<λ:K.F> CASE k OF Bind ⇒f0 | Flat f1⇒f1
<λ:C.F>
CASE CHead e (Flat f) u OF
CSort ⇒f0
| CHead k ⇒<λ:K.F> CASE k OF Bind ⇒f0 | Flat f1⇒f1
eq
F
λe1:C.<λ:C.F> CASE e1 OF CSort ⇒f0 | CHead k ⇒<λ:K.F> CASE k OF Bind ⇒f0 | Flat f1⇒f1
CHead e0 (Flat f0) u0
λe1:C.<λ:C.F> CASE e1 OF CSort ⇒f0 | CHead k ⇒<λ:K.F> CASE k OF Bind ⇒f0 | Flat f1⇒f1
CHead e (Flat f) u
end of H5
()
consider H5
we proved
eq
F
<λ:C.F>
CASE CHead e0 (Flat f0) u0 OF
CSort ⇒f0
| CHead k ⇒<λ:K.F> CASE k OF Bind ⇒f0 | Flat f1⇒f1
<λ:C.F>
CASE CHead e (Flat f) u OF
CSort ⇒f0
| CHead k ⇒<λ:K.F> CASE k OF Bind ⇒f0 | Flat f1⇒f1
eq F f0 f
end of
suppose H8: eq C e0 e
(H10)
we proceed by induction on H8 to prove clear e c
case refl_equal : ⇒
the thesis becomes the hypothesis H1
clear e c
end of H10
consider H10
we proved clear e c
(eq C e0 e)→(clear e c)
end of h1
(h2)
consider H4
we proved
eq
C
<λ:C.C> CASE CHead e0 (Flat f0) u0 OF CSort ⇒e0 | CHead c0 ⇒c0
<λ:C.C> CASE CHead e (Flat f) u OF CSort ⇒e0 | CHead c0 ⇒c0
eq C e0 e
end of h2
by (h1 h2)
we proved clear e c
∀H3:(eq C (CHead e0 (Flat f0) u0) (CHead e (Flat f) u)).(clear e c)
we proved (eq C y (CHead e (Flat f) u))→(clear e x)
we proved
∀y:C
.(clear y x)→(eq C y (CHead e (Flat f) u))→(clear e x)
by (insert_eq . . . . previous H)
we proved clear e x
we proved ∀f:F.∀e:C.∀x:C.∀u:T.(clear (CHead e (Flat f) u) x)→(clear e x)